2017
DOI: 10.1371/journal.pone.0184448
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of collagenase-1 (MMP1), stromelysin-1 (MMP3) and gelatinase-B (MMP9) gene polymorphisms in breast cancer

Abstract: BackgroundExtracellular matrix degradation by matrix metalloproteinases (MMPs) is an important mechanism involved in tumor invasion and metastasis. Genetic variations of MMPs have shown association with multiple cancers. The present study is focused to elucidate the association of MMP-1, 3 and 9 genetic variants with respect to epidemiological and clinicopathological variables by haplotype, LD, MDR, survival in silico analyses among South Indian women.Material and methodsMMP3–1171 5A/6A and MMP9–1562 C/T SNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 43 publications
4
41
0
1
Order By: Relevance
“…These results are in line with previous findings of AbdRaboh in 2016, who reported that 5A allele is associated with increased risk of BC in a sample of BC patients in UAE (23). In addition, Padala in 2017, reported that 5A/6A genotype increased the risk of BC development among Indian population (22).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in line with previous findings of AbdRaboh in 2016, who reported that 5A allele is associated with increased risk of BC in a sample of BC patients in UAE (23). In addition, Padala in 2017, reported that 5A/6A genotype increased the risk of BC development among Indian population (22).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, and along with investigating the variations in gene expression, SNPs analysis may be promising predictive and prognostic markers, which may lead to better management of the disease (18). Most of the reported SNPs in MMPs genes are functionally implicated in the progression of BC (19)(20)(21) particularly; those found in the promoter region and alter gene expression, which may result in imbalance in the MMP system, which, in turn, leads to excessive degradation of ECM and deregulation of ECM dynamics in cancer development (22).…”
Section: Discussionmentioning
confidence: 99%
“…5A/6A MMP-3 polymorphism was found to be significantly connected with lymph node metastases, which have influence to the survival rate of patients. 70 …”
Section: Mmp-3 In Carcinogenesis Of Cancersmentioning
confidence: 99%
“…FOXN3 suppresses MMP-9 secretion via the regulation of SIRT6 expression. MMP-9 can digest gelatins or denatured collagens (24), and has been reported to promote metastasis in some types of cancers (25,26). In addition, SIRT6 was proposed to regulate MMP-9 expression in OS and non-small cell lung cancer (27).…”
Section: Foxn3 Transcriptionally Regulates Sirt6 Expressionmentioning
confidence: 99%